2014
DOI: 10.1073/pnas.1423026112
|View full text |Cite
|
Sign up to set email alerts
|

Lunapark stabilizes nascent three-way junctions in the endoplasmic reticulum

Abstract: The endoplasmic reticulum (ER) consists of a polygonal network of sheets and tubules interconnected by three-way junctions. This network undergoes continual remodeling through competing processes: the branching and fusion of tubules forms new three-way junctions and new polygons, and junction sliding and ring closure leads to polygon loss. However, little is known about the machinery required to generate and maintain junctions. We previously reported that yeast Lnp1 localizes to ER junctions, and that loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
154
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(165 citation statements)
references
References 13 publications
8
154
1
Order By: Relevance
“…It is conceivable that the two ligases may function together to regulate a certain aspect of ER network construction by mediating ubiquitination of an unknown factor. Although our study does not reveal an apparent abnormality in ER morphology in gp78 CRISPR knock-out cells, it is noteworthy that the ER morphology change observed in Lnp knockdown mammalian cells is subtle (8). Thus, more sensitive assays are necessary to reveal the function of the Lnp-gp78 complex in ER morphology regulation.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…It is conceivable that the two ligases may function together to regulate a certain aspect of ER network construction by mediating ubiquitination of an unknown factor. Although our study does not reveal an apparent abnormality in ER morphology in gp78 CRISPR knock-out cells, it is noteworthy that the ER morphology change observed in Lnp knockdown mammalian cells is subtle (8). Thus, more sensitive assays are necessary to reveal the function of the Lnp-gp78 complex in ER morphology regulation.…”
Section: Discussioncontrasting
confidence: 56%
“…The Lnp homologous protein Lnp1p in budding yeast acts in conjunction with Rtn1p to antagonize Sey1p, the yeast homologue of Atlastin (9). Recently, it was reported that the localization of Lnp to the ER three-way junctions plays a role in stabilizing the polygonal network of the dynamic ER structure (8). Here, we identify Lnp as an interacting protein for the ER-anchored ubiquitin ligase gp78, an enzyme with a well established function in ER-associated protein quality control.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In metazoans and yeast, it has been shown that lunapark (Lnp1), a two-transmembrane domain protein, is required for ER shaping. In particular, Lnp1 has been implicated in contributing to the tubule-to-sheet conversion, most likely by stabilizing the three-way ER junctions (Chen et al, 2015;Wang S. et al, 2016). A functional ortholog of Lnp1 has yet to be identified in Arabidopsis, and it cannot be yet excluded that other proteins may have analogous functions to Lnp1 or that the stabilization of the plant ER junctions depends on different mechanisms compared with nonplant cell systems.…”
Section: Er Dynamics Depend On the Cytoskeleton And Er-shaping Proteinsmentioning
confidence: 99%
“…This translates to higher organisms as the same researchers determined that Lnp1 helps maintain ER structure in mammalian cells. Only 50% of junctions expressed Lnp1, but those that had Lnp1 were less dynamic 90 , indicating that junctions can form without Lnp1 but that they are less stable.…”
Section: Regulation Of Er Function and Morphologymentioning
confidence: 99%